2016
DOI: 10.1126/science.aaf0784
|View full text |Cite
|
Sign up to set email alerts
|

Prospective representation of navigational goals in the human hippocampus

Abstract: Mental representation of the future is a fundamental component of goal-directed behavior. Computational and animal models highlight prospective spatial coding in the hippocampus, mediated by interactions with the prefrontal cortex, as a putative mechanism for simulating future events. Using whole-brain high-resolution functional magnetic resonance imaging and multi-voxel pattern classification, we tested whether the human hippocampus and interrelated cortical structures support prospective representation of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
211
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(241 citation statements)
references
References 57 publications
18
211
1
1
Order By: Relevance
“…Posterior HPC has been shown to exhibit distinct representations for individual episodes, whereas anterior HPC codes for integrated representations that generalize across related episodes (8,22,38,54). The current study builds on these observations to show that anterior HPC representations are not limited to spatial contexts (19,38,55,56) or overlap between related episodes (8), but can also integrate attention-weighted object information across extended learning experiences. Our connectivity findings speculatively support the view that PFC interacts with HPC when concepts are updated to reflect changes in the learning context.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Posterior HPC has been shown to exhibit distinct representations for individual episodes, whereas anterior HPC codes for integrated representations that generalize across related episodes (8,22,38,54). The current study builds on these observations to show that anterior HPC representations are not limited to spatial contexts (19,38,55,56) or overlap between related episodes (8), but can also integrate attention-weighted object information across extended learning experiences. Our connectivity findings speculatively support the view that PFC interacts with HPC when concepts are updated to reflect changes in the learning context.…”
Section: Discussionmentioning
confidence: 84%
“…First, HPC rapidly learns (13), an ability important for updating conceptual representations in the face of changing goals. Second, HPC has also been shown to activate representations that are goal relevant (14)(15)(16)(17)(18)(19). A critical open question is how the same experiences come to be represented differently in neural terms as a function of changing conceptual knowledge.…”
mentioning
confidence: 99%
“…Indeed, the hippocampus exhibits anticipatory signals that can impact goal-directed behavior (e.g., Bornstein and Daw, 2013; Brown et al, 2016; Hindy et al, 2016; Johnson and Redish, 2007; Pfeiffer and Foster, 2013; for review, see Buckner, 2010; Redish, 2016). Given the increased coupling of posterior medial regions with the hippocampus, one speculation is that this may be contributing to hippocampal prediction.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have been extended to humans by using fMRI to scan participants while they perform a virtual navigation task: multi-voxel pattern analysis revealed that hippocampal activity patterns were linked to prospective navigational goals as participants planned their routes, and that the strength of these goal-related representations was associated with goal-related activity in other core network regions (105). Related work has shown, intriguingly, that imagined spatial navigation is accompanied by fMRI signals in entorhinal cortex that display features characteristic of grid cells (106).…”
Section: Functions Of Episodic Future Thinkingmentioning
confidence: 94%